CODE, CUL TURE & RAMSEY NASSER. - HAITHAM ENNASR (Kalimat Magazine)
An interview with New York City-based artist and designer Ramsey Nasser. The designer works for the Eyebeam Art & Technology center and is involved in Zajal, a creative coding language that was designed to reduce the contrast between creativity and software functioning. Previously, Nasser was involved with the Parsons Design and Technology program. He has also written Hello World and Conway's game of life in Qualb.